2015
DOI: 10.1177/0192513x15617797
|View full text |Cite
|
Sign up to set email alerts
|

Living With Parents and Emerging Adults’ Depressive Symptoms

Abstract: Whether moving back home after a period of economic independence, or having never moved out, the share of emerging adults living with parents is increasing. Yet little is known about the associations of coresidence patterns and rationales for coresidence for emerging adult well-being. Using the Toledo Adolescent Relationships Study (n = 891), we analyzed depressive symptoms among emerging adults who (1) never left the parental home; (2) returned to the parental home; and (3) were not currently living with a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 39 publications
5
56
0
4
Order By: Relevance
“…Prior to the pandemic, research highlighted that more young adults were living with their parents into their 20s and 30s; some of whom had never left, whereas others were returning to their parents' home ( (Billari and Liefbroer, 2007;Stone et al, 2011;Falkingham et al, 2016;Stone et al 2014). Further research had begun to shed light on the possible implications of intergenerational co-residence for the health and wellbeing of both older and younger generations (Copp, 2017;Tosi and Grundy, 2018). Some studies indicated a positive impact of co-residence with adult children on parents' well-being (Aranda, 2015;Courtin and Avendano, 2016), whereas others found that older parents living with adult children are more likely to report depressive symptoms or poor quality of life (Aquilino and Supple, 1991;Tosi and Grundy, 2018).…”
Section: Changing Living Arrangements Family Dynamics and Stress Durmentioning
confidence: 99%
“…Prior to the pandemic, research highlighted that more young adults were living with their parents into their 20s and 30s; some of whom had never left, whereas others were returning to their parents' home ( (Billari and Liefbroer, 2007;Stone et al, 2011;Falkingham et al, 2016;Stone et al 2014). Further research had begun to shed light on the possible implications of intergenerational co-residence for the health and wellbeing of both older and younger generations (Copp, 2017;Tosi and Grundy, 2018). Some studies indicated a positive impact of co-residence with adult children on parents' well-being (Aranda, 2015;Courtin and Avendano, 2016), whereas others found that older parents living with adult children are more likely to report depressive symptoms or poor quality of life (Aquilino and Supple, 1991;Tosi and Grundy, 2018).…”
Section: Changing Living Arrangements Family Dynamics and Stress Durmentioning
confidence: 99%
“…However, this transition has become more protracted and nonlinear in the United States and Europe, with increasing proportions of young adults boomeranging back to the parental home (South & Lei, ; Wobma & de Graaf, ). Recent studies have sought to explain this trend in terms of broader changes in the life course experiences of young adults, including economic uncertainty arising from precarity in the youth labor market, lack of affordability in the housing market, and the instability of partnerships (Copp, Giordano, Longmore, & Manning, ; Sandberg‐Thoma, Snyder, & Jang, ; Stone, Berrington, & Falkingham, ). Returning home can have negative implications, impacting relationships with parents, peers, and intimate partners (Lewis, West, Roberts, & Noden, ; Sassler, Ciambrone, & Benway, ).…”
mentioning
confidence: 99%
“…The implications of returning home for young adults and their parents depend on the reason for returning. Extended coresidence has been found to be associated with declines in parent and child well‐being in situations where returning home coincides with negative events such as job loss (Copp et al, ; Davis, Kim, & Fingerman, ). It is thus important to gain a deeper understanding of the life course events that trigger returns home and how they differ according to individual and parental characteristics.…”
mentioning
confidence: 99%
“…On the one hand, returning to the parental home protects young adults against labor market risks, offers emotional and financial support, and indicates a good relationship with the parents (Kaplan, ; Lewis, West, Roberts, & Noden, ). On the other hand, returning is sometimes regarded as a sign of failure (Pickhardt, ) and could negatively impact well‐being, relationships, and parental savings (Copp, Giordano, Longmore, & Manning, ; Lewis et al, ; Maroto, ; Tosi & Grundy, ).…”
Section: Introductionmentioning
confidence: 99%